PERENCANAAN TEBAL PERKERASAN KAKU (RIGID PAVEMENT) DENGAN METODE BINA MARGA (STUDI KASUS PENINGKATAN JALAN DURIAN RAYA KOTA SEMARANG) - Nugroho, Yuniar Anang; Wibowo, Untung (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
Semarang in the development of the next 20-50 years will experience many impacts of delays in traffic movement in it. To overcome the various impacts that arise, the development of a road network is an important option. The alternative choice of road network development solutions must be selective in choosing the location. One of the strategic choices at this time is the Outer Ring Road (outer ring road) Semarang. The Outer Ring Road is expected to divert the continuous flow not through the center of Semarang City, thereby reducing the possibility of delays in the center of Semarang City. This alternative is also expected to develop the Semarang City area. This alternative solution is expected to support the development of Semarang City into a Metropolitan City with smooth traffic movement. The development of Semarang City in the next 20-50 years is expected to be more friendly and provide a sense of security and comfort to its residents as expected in the vision of the City of Semarang (Nugroho, 2009). Physical facilities and infrastructure (infrastructure) in an area are very important and vital for the running of the economic wheels of the local community, the accumulation of increasing people's living standards will be driven automatically by the good or bad conditions and conditions of the existing facilities and infrastructure. One of these infrastructure facilities which quite main is the road. With good road infrastructure, it is easier to access from one place to another, so that economic growth in the area will be faster. Where on Jl. Durian Banyumanik Semarang city is an access road for entry and exit from the Banyumanik toll gate to the southern part of the city of Semarang, to be precise towards Jl. Setia Budi, Jalan Durian Banyumanik, is planned by the City Government to later become one of the supporting roads for the Semarang Outer Ring Road (SORR).Keywords: Semarang, SORR, facilities, infrastructure